Implementasi Penilaian Autentik Dalam Pembelajaran Ekonomi Pada Kurikulum Merdeka: Suatu Studi Literatur - Muhammad Bukhori Dalimunthe; Deni Adriani; Widia Gultom; Maynisa Naomi Marpaung; Egi Malemta Gunana Sebayang; Cristina Matalia Sitepu (Universitas Hamzanwadi, 2026)
The purpose of this research is to conduct a literature review related to authentic assessment of economics learning in the Merdeka Curriculum. The research approach used a qualitative approach by exploring literature from credible sources related to the issue of authentic assessment of economics learning in the Merdeka Curriculum. A literature review was used as the data analysis technique in this article. Through a literature review, the review aims to map current research, synthesize research findings, identify best practices, and identify research gaps that will be filled by future researchers. Using a qualitative approach through content analysis and thematic synthesis, this study examines 15 articles consisting of nationally indexed (Sinta=8) and internationally indexed (Scopus=7) journals accredited in 2018–2025. Results show authentic assessment, based on realism, cognitive challenge, and evaluative judgment, aligns with Merdeka Curriculum and the Pancasila Student Profile. Forms include performance, project, portfolio, and contextual written assessments. Challenges involve teacher competence, student readiness, and infrastructure support. Opportunities arise from curriculum flexibility, current issues, and technology, improving learning outcomes, 21st-century skills, motivation, and engagement.